Hemodynamic numerical simulation of aortic arch modular inner branched stent-graft in eight early patients from the first-in-human case series - Zhu, Yating; Li, Fen; Zhang, Hongpeng; Song, Hui; Ma, Xiaodan; Cao, Long; Zhang, Wenjun; Guo, Wei (Frontiers in Cardiovascular Medicine, 2022)
Background The modular inner branched stent-graft (MIBSG, WeFlow ArchTM) is an emerging device for the challenging aortic arch pathologies. Hemodynamic numerical simulation is conducive to predicting the long-term outcomes as well as optimizing its designs. Objectives To summary the early results of MIBSG utilization in the first-in-human cases and analyze their hemodynamic characteristics based on numerical simulation. Methods From June 2019 to June 2021, MIBSG were utilized in eight first-in-human cases. Numerical simulation analyses of both branches perfusions and indicators including time averaged wall shear stress, oscillatory shear index, and relative residence time were performed. Results Lesions involved Zone 1 (n=2), Zone 2 (n=4), Zone 3 (n=2). Branch stent-grafts were deployed in innominate artery (IA) and left common carotid artery (LCCA) (n=5), or IA and left subclavian artery (LSA) (n=3). The primary technical success rate was 100%. One immediate type-I endoleak was observed, which disappeared in 6-months follow-ups. No death, stroke, stent occlusion, or stent-graft induced new entry was documented during the follow-ups (range, 9-33 months). The hemodynamic changes in common included increased perfusions in descending aorta and LCCA. Half of the patients had increased cerebral perfusion with 8.7 percent at most and the others appeared as reduction with 5.3 percent or less. Case 3 was considered to acquiring the best improvement in hemodynamic features. Conclusions The MIBSG devices showed promising early-term results in the 8 first-in-human cases with improved hemodynamic features in most cases. Designs of MIBSG could be partly modified to acquire better hemodynamic performance.